Effect of logging on tree structure and diversity in tropical forests of Quintana Roo, Mexico - Tadeo-Noble, Alfredo Esteban; Valdez-Hernández, Juan Ignacio; Beltrán-Rodríguez, Leonardo; García-Moya, Edmundo (BOSQUE, 2019)
Timber harvesting may lead to changes in the dasonomic and ecological attributes of tree vegetation, affecting the productivity and biodiversity of ecosystems. Although, little is known about the effect of this practice on the tropical forests of Mexico. The aim was to compare the structure and diversity in forest ejidos under timber harvesting in Quintana Roo. Two inventories (2009) were developed in Permanent Forest Areas (PFA) of medium evergreen forests. In Bacalar, 625 plots of 10x25 m distributed in 15.6 ha were used, while in Noh Bec 302 plots of 10x40m located in 48.32 ha. In each plot, all trees with normal diameter ≥ 7.5 cm were measured to document richness and dasometric variables. Structural indexes (IVI and FMVI) and diversity indexes (Shannon-Wiener H’ and Sorensen Cs) were also calculated. In Bacalar there were 86 tree species (36 families and 81 genera), 284 tree ha-1, 7.3 m2 ha-1 of BA and 86.4 m3 ha-1 of TTV; whereas in Noh Bec, we registered 106 species (34 families and 94 genera), 625 individuals ha-1, 23.9 m2 ha-1 of BA and 183.8 m3 ha-1 of TTV. Bursera simaruba (IVI= 16.6 %, FMVI= 18.1 %) was the dominant species in Bacalar, whereas in Noh Bec it was Pouteria reticulata (IVI= 13.5 %, FMVI= 14.8 %). The species diversity was not different (P > 0.05) between ejidos (H’= 3.48 vs H’= 3.37); nonetheless there was a high floristic similarity (Cs= 60.4 %). Our results provide evidence that timber harvesting associated with the history of natural disturbances drives a key role in the structure and diversity of tropical forests.